Mary Lennox Impoliteness Strategy in movie “The Secret Garden 2020” - Suhenda, Ledise; Marlina, Leni (English Language and Literature, 2024)
This study was motivated by the phenomenon of rude and cold speech patterns carried out by the main character of the children's story in the film The Secret Garden 2020. This study aims to analyse the types and triggers of Impoliteness Strategies carried out by the main character. In children's stories, there tend to be main characters who are friendly and kind so that they can be examples for their readers. However, unlike the story from the novel "The Secret Garden" by F.H. Burnett, the main character of this story is an unfriendly child, therefore the researcher wants to know what triggers the unfriendly attitude of the main character, as well as what forms of impoliteness are carried out by the main character. The researcher chose the 2020 film adaptation as the data source for this study. The story adaptation of the novel "The Secret Garden" version of 2020 presents a story through audio-visuals that can be observed carefully. Data collection was carried out by analysing the script of the film The Secret Garden 2020. The researcher collected utterances that were estimated to contain types of impoliteness strategies according to the theory of "Impoliteness Strategy" introduced by Culpeper (1996). The results of the study showed that there was the use of three of the five types of impoliteness strategies found, namely as well as several triggers for impoliteness strategy actions.